ANALISIS PRODUKSI DAN PEMASARAN GULA MERAH DI DESA KUBANGKANGKUNG, KABUPATEN CILACAP - Fajri Efendi; Pujiharto, Pujiharto,; Dumasari Dumasari (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2017)
The purpose of this study is (1) to know the process of producing brown sugar made by craftsmen in the village of Kubangkangkung, Kawunganten district, Cilacap City, (2) to find out the social-economic factors that affect the production process and the marketing process of brown sugar in the village of Kubangkangkung, Kawunganten district, Cilacap City, (3) to fint out the problems and solutions faced by farmers during the process of producing and marketing brown sugar in the village of Kubangkangkung, Kawunganten district, Cilacap City, (4) to analyze the marketing process of brown sugar in the village of Kubangkangkung, Kawunganten district, Cilacap City. This research uses primary and secondary analysis. Research method used by researcher is using survey method with respondent 35. In marketing channel there are 3 marketing channel so that will know difference of price, profit, and channel effective for brown sugar artisans.